Method for producing polyamide-based resin-foamed particle, and method for producing polyamide-based resin foam-molded product

By combining specific organic and iodide additives in the production process, polyamide resin foam particles achieve improved moldability and surface properties, addressing moldability issues in existing technologies.

JP2025018592APending Publication Date: 2025-02-06JSP CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023122443
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Existing polyamide-based resin foam molded articles face issues with moldability, particularly poor secondary foaming properties and surface properties, especially at corners, when heat-resistant agents like copper iodide are used.

Method used

A method involving the use of polyamide resin with specific ratios of organic compound additives, such as hindered phenolic compounds and organophosphorus compounds, combined with iodide additives like copper iodide or copper and potassium iodide, during melt kneading and foaming, to produce polyamide resin foam particles with improved moldability and surface properties.

Benefits of technology

The method results in polyamide resin foam particles with enhanced heat resistance, moldability, and superior surface properties, allowing for the production of molded articles with reduced shrinkage and excellent light weight, even at low molding pressures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018592000001
    Figure 2025018592000001
  • Figure 2025018592000002
    Figure 2025018592000002
  • Figure 2025018592000003
    Figure 2025018592000003
Patent Text Reader

Abstract

To provide a method for producing polyamide-based resin-foamed particles for producing a polyamide-based resin foam-molded product excellent in heat resistance and reduction in weight with excellent moldability, and to provide a method for producing a polyamide-based resin foam-molded product using the polyamide-based resin-foamed particles.SOLUTION: A method for producing polyamide-based resin-foamed particles includes: obtaining polyamide-based resin particles by pelletizing a polyamide-based resin molten material obtained by melting and kneading a base resin, an organic compound-based additive (A) and an iodinated additive (X); and obtaining polyamide-based resin-foamed particles by foaming the polyamide-based resin particles using a physical foaming agent. A polyamide-based resin foam-molded product is produced by in-mold molding polyamide-based resin-foamed particles. The organic compound-based additive (A) comprises a hindered phenolic compound and / or an organic phosphorus compound. The iodinated additive (X) comprises copper iodide, or copper iodide and potassium iodide.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing expanded polyamide resin particles using a polyamide resin as a base resin, and a method for producing an expanded molded polyamide resin article. [Background technology]

[0002] Polyamide resins are known as resins that have high heat resistance and are also excellent in abrasion resistance, chemical resistance, etc. A foam molded product obtained by foaming this polyamide resin can be made lighter while maintaining excellent properties such as heat resistance, abrasion resistance, and chemical resistance, etc. Therefore, polyamide resin foam molded products are expected to be used in automobile parts and other applications.

[0003] In order to further improve the heat resistance of polyamide resin foamed molded bodies, the addition of heat-resistant agents such as copper iodide has been considered. For example, Patent Document 1 proposes a technique for incorporating a base metal element-containing compound into polyamide resin foamed beads, and according to Patent Document 1, this technique makes it possible to obtain polyamide resin foamed beads with excellent thermal stability. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2020 / 196893 Summary of the Invention [Problem to be solved by the invention]

[0005] However, although the heat resistance of the polyamide resin foamed molding is improved by adding a base metal element-containing compound such as copper iodide, there is still room for improvement in moldability. Specifically, when attempting to obtain a molded product by molding polyamide resin foamed beads containing a heat-resistant agent such as copper iodide in a mold, the secondary foamability is poor, and the gaps between the foamed beads are not filled, resulting in poor surface properties of the molded product, leaving room for improvement in the surface properties of the molded product. In particular, there is a problem that the corners of the molded product are prone to have poor secondary foamability and poor surface properties.

[0006] The present invention has been made in view of the above background, and aims to provide a method for producing polyamide-based resin foamed beads, which can produce polyamide-based resin foamed molded articles having excellent heat resistance and excellent moldability, and a method for producing polyamide-based resin foamed molded articles using the polyamide-based resin foamed beads. [Means for solving the problem]

[0007] One aspect of the present invention resides in a method for producing expanded polyamide resin beads according to the following items [1] to [5]. [1] A method for producing expanded polyamide-based resin beads using a polyamide-based resin as a base resin, comprising the steps of: a step of preparing polyamide-based resin particles by granulating a polyamide-based resin melt obtained by melt-kneading the base resin, an organic compound-based additive (A) consisting of a hindered phenol compound and / or an organic phosphorus compound, and an iodide-based additive (X) consisting of copper iodide or copper iodide and potassium iodide; and a step of expanding the polyamide-based resin particles using a foaming agent to obtain expanded polyamide-based resin particles, the amount of the organic compound-based additive (A) added is 0.05 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the base resin, A method for producing expanded polyamide resin particles, wherein the ratio of the amount of the organic compound-based additive (A) to the amount of the iodide-based additive (X) is 0.3 or more and 7 or less.

[0008] [2] The method for producing expanded polyamide resin particles according to [1], wherein the ratio of the amount of the organic compound-based additive (A) to the amount of the iodide-based additive (X) is 1 or more and 4 or less. [3] The method for producing expanded polyamide resin beads according to [1] or [2], wherein the polyamide resin melt contains the hindered phenol compound (A1) and the organophosphorus compound (A2) as the organic compound additive (A), and the ratio of the amount of the organophosphorus compound (A2) to the amount of the hindered phenol compound (A1) is 0.5 or more and 2 or less. [4] The method for producing expanded polyamide resin particles according to any one of [1] to [3], wherein the amount of the iodide additive (X) added is 0.1 parts by mass or more per 100 parts by mass of the base resin. [5] The method for producing expanded polyamide resin particles according to any one of [1] to [4], wherein the polyamide resin melt further contains carbon black, and the amount of the carbon black added is 0.5 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the base resin.

[0009] Another aspect of the present invention resides in a method for producing a polyamide resin foam molded article according to the following item [6]. [6] A method for producing a polyamide resin foamed molded article, comprising molding in a mold the expanded polyamide resin beads produced by the method according to any one of [1] to [5]. Effect of the Invention

[0010] According to the method for producing expanded beads, a method for producing expanded polyamide resin beads capable of producing a polyamide resin expanded molded article having excellent heat resistance with excellent moldability can be provided. Also, according to the method for producing a molded article, a method for producing an expanded polyamide resin bead molded article having excellent heat resistance with excellent moldability can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In this specification, "polyamide-based resin particles" may be referred to as "resin particles," "polyamide-based resin expanded particles" may be referred to as "expanded particles," and "polyamide-based resin expanded molded body" may be referred to as "molded body." In addition, when the symbol "~" is used to express a numerical range, it is used in a sense including the numerical values ​​written before and after it.

[0012] [Method of manufacturing foam beads] The expanded beads are produced by the following preparation step and expansion step, and are used, for example, for producing a molded body. The preparation step is a step of preparing polyamide-based resin particles. In the preparation step, a base resin, an organic compound-based additive (A) consisting of a hindered phenol-based compound (A1) and / or an organic phosphorus-based compound (A2), and an iodide-based additive (X) consisting of copper iodide or copper iodide and potassium iodide are melt-kneaded to produce a polyamide-based resin melt, which is then granulated. In the preparation step, all operations can be performed in a single step, but the preparation step can also be divided into, for example, a melt-kneading step and a granulation step, as described below.

[0013] In the melt-kneading step, a base resin, an organic compound additive (A), and an iodide additive (X) are melt-kneaded to obtain a polyamide resin melt. The organic compound additive (A) means an organic compound consisting of a hindered amine compound and / or an organic phosphorus compound, and is a concept that does not include organic compounds other than the hindered amine compound and the organic phosphorus compound. The iodide additive (X) means copper iodide or a metal iodide consisting of copper iodide and potassium iodide, and is a concept that does not include metal iodides other than copper iodide and potassium iodide. Note that the iodide additive (X) means copper iodide when potassium iodide is not used, and means copper iodide and potassium iodide when potassium iodide is used together with copper iodide. In the granulation step, the polyamide resin melt is granulated to obtain polyamide resin particles. In the expansion step, the polyamide resin particles are expanded using a foaming agent to obtain expanded polyamide resin particles. Each step will be described in detail below.

[0014] <Melting and kneading process> Base resin In the melt-kneading step, a polyamide-based resin is used as the base resin of the expanded beads, and the base resin is melt-kneaded together with an organic compound-based additive (A) and an iodide-based additive (X). The base resin means, for example, a resin whose content exceeds 50% by mass among the resins constituting the expanded beads. The content of the polyamide-based resin among the resins constituting the expanded beads is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. It is particularly preferable that the resin constituting the expanded beads is substantially composed of only a polyamide-based resin.

[0015] As the polyamide-based resin, for example, polyamide and polyamide copolymer are used. Polyamides include, for example, poly(6-aminohexanoic acid), also known as poly(caprolactam) (also known as polycaproamide, nylon 6), poly(laurolactam) (also known as nylon 12), poly(hexamethylene adipamide) (also known as nylon 66), poly(7-aminoheptanoic acid) (also known as nylon 7), poly(8-aminooctanoic acid) (also known as nylon 8), poly(9-aminononanoic acid) (also known as nylon 9), poly(10-aminodecanoic acid) (also known as nylon 10), poly(11-aminoundecanoic acid) (also known as nylon 11), and poly(12-aminobutanoic acid) (also known as nylon 12). Examples of such homopolymers include poly(hexamethylene sebacamide) (also known as nylon 11), poly(hexamethylene sebacamide) (also known as nylon 610), poly(decamethylene sebacamide) (also known as nylon 1010), poly(hexamethylene azelamide) (also known as nylon 69), poly(tetramethylene adipamide) (also known as nylon 46), poly(tetramethylene sebacamide) (also known as nylon 410), poly(pentamethylene adipamide) (also known as nylon 56), and poly(pentamethylene sebacamide) (also known as nylon 510). A polyamide copolymer refers to a copolymer having two or more types of repeating units, with at least a portion of each repeating unit having an amide bond. Examples of polyamide copolymers include polycaproamide / polyhexamethylene adipamide copolymer (also known as nylon 6 / 66), caprolactam / hexamethylenediaminoadipic acid / lauryl lactam (also known as nylon 6 / 66 / 12) copolymer, and caprolactam / lauryl lactam copolymer (also known as nylon 6 / 12). The polyamide resin may be one of these polyamides and polyamide copolymers, or two or more of them may be used in combination. Among the above polyamide resins, at least one selected from the group consisting of nylon 6, nylon 66, nylon 6 / 66, and nylon 6 / 66 / 12 is preferred, and nylon 6 / 66 and / or nylon 6 / 66 / 12 is more preferred.

[0016] The polyamide copolymer may be a block copolymer in which a certain amount of amides of the same repeating unit are followed by a certain amount of amides of different types, or a random copolymer in which different types of amides are randomly repeated, but is preferably a random copolymer. If the polyamide copolymer is a random copolymer, it becomes possible to mold the expanded beads at a lower molding pressure when molding them in a mold.

[0017] The polyamide resin may be a terminal-blocked polyamide resin in which the functional groups at the molecular chain ends are blocked, which makes it possible to more reliably suppress hydrolysis during the production process of the expanded beads, and makes it easier to obtain expanded beads that can withstand in-mold molding.

[0018] A terminal blocking agent can be used to block the molecular chain ends. Examples of terminal blocking agents include carbodiimide compounds, oxazoline compounds, isocyanate compounds, and epoxy compounds, among which carbodiimide compounds are preferred. Specific examples include aromatic monocarbodiimides such as bis(dipropylphenyl)carbodiimide (e.g., "Stabaxol 1-LF" manufactured by Rhein Chemie), aromatic polycarbodiimides (e.g., "Stabaxol P", "Stabaxol P100", "Stabaxol P400" manufactured by Rhein Chemie), and aliphatic polycarbodiimides such as poly(4,4'-dicyclohexylmethanecarbodiimide) (e.g., "Carbodilite LA-1" manufactured by Nisshinbo Chemical Co., Ltd.). These terminal blocking agents may be used alone or in combination of two or more.

[0019] The amount of the end blocking agent is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 3 parts by mass, based on 100 parts by mass of the polyamide resin.

[0020] Other thermoplastics In the melt-kneading step, in addition to the polyamide-based resin as the base resin, other thermoplastic resins can be added within a range that does not impair the object and effect of the present invention. Examples of other thermoplastic resins include polyethylene-based resins, polypropylene-based resins, polystyrene-based resins, vinyl acetate resins, thermoplastic polyester resins, acrylic acid ester resins, methacrylic acid ester resins, modified polyphenylene ether resins, polycarbonate resins, polyacetal resins, polybutylene terephthalate resins, polysulfone resins, polyethersulfone resins, polyamideimide resins, polyetherimide resins, polyetheretherketone resins, polyarylene sulfide-based resins, etc.

[0021] Organic compound additives (A), iodide additives (X) In the melt-kneading step, a hindered phenol compound (A1) and / or an organic phosphorus compound (A2) is used as the organic compound additive (A). The organic compound additive (A) is used, for example, as an antioxidant for the expanded beads. In addition, in the melt-kneading step, copper iodide or copper iodide and potassium iodide is used as the iodide additive (X). The iodide additive (X) is used, for example, as a heat resistance agent for the expanded beads having a polyamide resin as a base resin. Conventionally, in the case of expanded beads using a polyamide resin as a base resin, the secondary expandability of the expanded beads is insufficient, and the surface properties of the molded article are poor. In particular, in the corners of the molded article, the secondary expandability is poor, and the surface properties of the molded article are poor. In the present disclosure, it has been found that the heat resistance of the polyamide resin expanded bead molded article is improved and the secondary expandability is improved by using the organic compound additive (A) and the iodide additive (X). As a result, a polyamide resin expanded bead molded article having good surface properties and excellent moldability is obtained. In addition, it has been found that the molding pressure conditions tend to be particularly wide on the low pressure side, and molding at low pressure is possible, and molding can be performed with a small amount of heating medium, so that the heating medium required during molding can be reduced. Furthermore, it has been found that the synergistic effect of the organic compound additive (A) and the iodide additive (X) enables high expansion ratios and improves the lightweight properties of the molded article.

[0022] The reason why the moldability is improved by using the organic compound additive (A) and the iodide additive (X) in combination is considered to be as follows. The step of obtaining a polyamide resin melt by melt-kneading the base resin, the organic compound additive (A), and the iodide additive (X) is performed, for example, by feeding the base resin, the organic compound additive (A), and the iodide additive (X) to an extruder and melt-kneading them in the extruder. At this time, in general, in order to melt-knead the base resin, the organic compound additive (A), and the iodide additive (X) sufficiently, the melt is kneaded near the melting point of the base resin to obtain a resin melt. When performing the melt-kneading, the presence of the organic compound additive (A) and the iodide additive (X) suppresses the scission of the molecular chain of the polyamide resin, and the inherent foaming performance of the polyamide resin can be maintained, which is considered to improve the secondary foaming property during molding, and obtain polyamide resin expanded particles having a wide moldable pressure range and excellent moldability. In addition, since the molecular chain scission of the polyamide resin is suppressed, expanded beads having excellent light weight can be obtained, and since the secondary foaming property during molding is improved, an expanded bead molding having excellent light weight can be obtained. Regarding the effect of improving moldability, even at the corners of a molded article which is difficult to mold, an expanded polyamide resin bead molding having excellent secondary foaming property and excellent surface properties can be obtained. In in-mold molding, excellent secondary foaming property at the corners of a molded article means that a molded article having excellent moldability can be obtained even for a thick molded article or a molded article having a complex shape having a thick part and a thin part.

[0023] In addition, the process of obtaining expanded polyamide resin particles by expanding polyamide resin particles using a foaming agent is carried out, for example, by a dispersion process in which resin particles are dispersed in a liquid such as water in a sealed container to obtain a dispersion liquid, an impregnation process in which the resin particles in the dispersion liquid are impregnated with a foaming agent, and an expansion process (in other words, an opening process) in which the resin particles containing the foaming agent are released from the sealed container together with water under a pressure lower than the pressure in the sealed container to expand them. In particular, when the resin particles are dispersed in water, the polyamide resin particles are plasticized and easily hydrolyzed. In the manufacturing method having the dispersion process, the organic compound additive (A) and the iodide additive (X) are present, the molecular chain of the polyamide resin is more suppressed from being cut, which improves the secondary foaming property during molding, and it is considered that the expanded polyamide resin particles having excellent moldability are easily obtained.

[0024] The amount of the organic compound additive (A) added relative to 100 parts by mass of the base resin is 0.05 parts by mass or more and 5 parts by mass or less. If the amount of the organic compound additive (A) added is less than 0.05 parts by mass, the moldability improving effect and the light weight improving effect may be insufficient. On the other hand, if the amount added is more than 5 parts by mass, the moldability may be reduced. From the same viewpoint, the amount of the organic compound additive (A) added relative to 100 parts by mass of the base resin is preferably 0.1 parts by mass or more and 3 parts by mass or less, and more preferably 0.1 parts by mass or more and 1.5 parts by mass or less. From the viewpoint of lowering the shrinkage rate of the molded body while maintaining a wider moldable pressure range, it is more preferable that the amount of the organic compound additive (A) added is 0.3 parts by mass or more and 1 part by mass or less. The amount of the organic compound additive (A) added is the sum of the amount of the hindered phenol compound (A1) added and the amount of the organic phosphorus compound (A2) added, and includes the case where either one of the amounts added is 0.

[0025] The organic compound additive (A) preferably contains both the hindered phenol compound (A1) and the organic phosphorus compound (A2). It is more preferable that the organic compound additive (A) contains the hindered phenol compound (A1) and the organic phosphorus compound (A2), and the ratio of the amount of the organic phosphorus compound (A2) to the amount of the hindered phenol compound (A1) is 0.5 or more and 2 or less. When the ratio of the amount of the organic phosphorus compound (A2) to the amount of the hindered phenol compound (A1) satisfies a specific range, the hydrolysis of the polyamide resin can be further prevented by the synergistic effect of the organic compound additive (A) and the iodide additive (X), and it is possible to obtain expanded beads having excellent lightness. From the viewpoint of further enhancing this effect, when the organic compound additive (A) contains a hindered phenol compound (A1) and an organic phosphorus compound (A2), the ratio of the amount of the organic phosphorus compound (A2) added to the amount of the hindered phenol compound (A1) added is more preferably 0.7 or more and 1.5 or less, and even more preferably 0.8 or more and 1.3 or less.

[0026] The hindered phenol compound (A1) preferably has 2 to 6 hindered phenol structures, more preferably has 2 hindered phenol structures. The hindered phenol compound preferably has an amide bond, more preferably a hindered hindered phenol compound having an amide bond. When the hindered amine compound is a hindered phenol compound having an amide bond, the hindered amine compound preferably has 2 to 6 amide bonds and 2 to 6 hindered hindered phenol structures, more preferably has 2 to 6 di-tert-butyl-4 hydroxyphenyl alkyl carbonyl amide groups, and the number of carbon atoms in the alkyl chain portion in the di-tert-butyl-4 hydroxyphenyl alkyl carbonyl amide group is preferably 1 to 5, more preferably 2 to 4. The hindered phenol compound is particularly preferably N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4 hydroxyphenyl propionamide], which is a compound represented by the following general formula (1).

[0027] [ka]

[0028] Examples of the organic phosphorus compound (A2) that can be used include phosphite triesters, such as tris(isodecyl)phosphite, tris(tridecyl)phosphite, phenyl isooctyl phosphite, phenyl isodecyl phosphite, phenyl di(tridecyl)phosphite, diphenyl isooctyl phosphite, diphenyl isodecyl phosphite, diphenyl tridecyl phosphite, triphenyl phosphite, tris(nonylphenyl)phosphite, 4,4'isopropylidenediphenol alkyl phosphite, trisnonylphenyl phosphite, tris(dinonylphenyl)phosphite, tris(2,4-di-t-butylphenyl)phosphite, tris(biphenyl)phosphite, distearyl pentaerythritol diphosphite, di(2,4-di-t-butyl di(nonylphenyl)pentaerythritol diphosphite, di(nonylphenyl)pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, tetratridecyl 4,4'-butylidenebis(3-methyl-6-t-butylphenol) diphosphite, hexatridecyl 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane triphosphite, 3,5-di-t-butyl-4-hydroxybenzyl phosphite diethyl ester, sodium bis(4-t-butylphenyl)phosphite, sodium-2,2-methylene-bis(4,6-di-t-butylphenyl)-phosphite, 1,3-bis(diphenoxyphosphonyloxy)-benzene, ethyl bis(2,4-ditert-butyl-6-methylphenyl) phosphite, and the like. In addition, oligomer-type and polymer-type compounds having a phosphite structure can also be used. As the organic phosphorus compound, tris(2,4-di-t-butylphenyl)phosphite represented by the following general formula (2) is preferable.

[0029] [ka]

[0030] The organic compound additive (A) consisting of a hindered phenol compound (A1) and / or an organic phosphorus compound (A2) is used, for example, as an antioxidant for the expanded beads. The base resin may contain other antioxidants than the hindered phenol compound (A1) and the organic phosphorus compound (A2) within a range that does not impair the object and effect of the present invention. As the other antioxidant, a sulfur-based antioxidant, a thioether-based antioxidant, etc. can be used.

[0031] The ratio of the amount of the organic compound additive (A) to the amount of the iodide additive (X) (i.e., the ratio of the total amount of the hindered phenol compound (A1) and the organic phosphorus compound (A2) to the total amount of the copper iodide and potassium iodide) is 0.3 or more and 7 or less. If the ratio of the amounts is less than 0.3, the moldability may be insufficient. On the other hand, if the ratio of the amounts is more than 7, the moldability of the expanded beads may be insufficient, and the heat resistance of the molded body may be insufficient, resulting in large shrinkage in a high-temperature environment. From the same viewpoint, the ratio of the amount of the organic compound additive (A) to the amount of the iodide additive (X) is preferably 0.5 or more and 5 or less, more preferably 1 or more and 4 or less, and even more preferably 1.5 or more and 3 or less. The amount of the copper iodide additive (X) is the sum of the amount of the copper iodide and the amount of the potassium iodide, and includes the case where either one of the amounts is 0.

[0032] The iodide-based additive (X) is composed of copper iodide or copper iodide and potassium iodide as described above. That is, as the iodide-based additive (X), at least copper iodide is used, and potassium iodide can also be used together with copper iodide.

[0033] The amount of the iodide-based additive (X) added to 100 parts by mass of the base resin is preferably 0.01 parts by mass or more and 1 part by mass or less. In this case, a molded product having better heat resistance can be obtained. From the same viewpoint, the amount of the iodide-based additive added to 100 parts by mass of the base resin is more preferably 0.02 parts by mass or more and 0.5 parts by mass or less, and further preferably 0.03 parts by mass or more and 0.2 parts by mass or less.

[0034] From the viewpoint of improving the flame retardancy and further improving the above-mentioned effect by using the copper iodide-based additive (X) and the organic compound-based additive (A) in combination, the iodide-based additive (X) is preferably composed of copper iodide and potassium iodide. The ratio of the amount of potassium iodide added to the amount of copper iodide added is preferably 0.5 or more and 20 or less. In this case, even if the amount of the iodide-based additive (X) added is small, a molded product with better heat resistance can be obtained. From the same viewpoint, the ratio of the amount of potassium iodide added to the amount of copper iodide added is more preferably 1 or more and 10 or less, and even more preferably 2 or more and 6 or less.

[0035] As described above, the iodide additive (X) can function as a flame retardant, but in the melt-kneading step, a flame retardant consisting of a metal halide other than the iodide additive (X) can be added within a range that does not impair the object and effect of the present invention. In this case, the amount of the iodide additive (X) added in the metal halide is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more, and it is particularly preferable that the metal halide is substantially composed of the iodide additive (X).

[0036] Examples of metal halides other than the iodide-based additive (X) include alkali metal halides such as lithium iodide, sodium iodide, lithium bromide, sodium bromide, potassium bromide, lithium chloride, sodium chloride, and potassium chloride; alkaline earth metal halides such as magnesium iodide, calcium iodide, magnesium bromide, calcium bromide, magnesium chloride, and calcium chloride; Group 7 metal halides such as manganese (II) iodide, manganese (II) bromide, and manganese (II) chloride; Group 8 metal halides such as iron (II) iodide, iron (II) bromide, and iron (II) chloride; Group 9 metal halides such as cobalt (II) iodide, cobalt (II) bromide, and cobalt (II) chloride. Examples of the metal halide include: Group 10 metal halides such as nickel (II) iodide, nickel (II) bromide, and nickel (II) chloride; Group 11 metal halides such as copper (I) bromide and copper (I) chloride; Group 12 metal halides such as zinc iodide, zinc bromide, and zinc chloride; Group 13 metal halides such as aluminum (III) iodide, aluminum (III) bromide, and aluminum (III) chloride; Group 14 metal halides such as tin (II) iodide, tin (II) bromide, and tin (II) chloride; Group 15 metal halides such as antimony triiodide, antimony tribromide, antimony trichloride, bismuth (III) iodide, bismuth (III) bromide, and bismuth (III) chloride. As the other metal halides, one of these can be used, or two or more can be used in combination. From the viewpoints of further improving moldability, reducing costs, and reducing adverse effects on the environment and living organisms, the metal constituting the metal halide is preferably copper or zinc, and from the viewpoint of further improving heat resistance, the halogen constituting the metal halide is preferably iodine.

[0037] The amount of metal halide added (specifically, the total amount of iodide-based additive (X) and metal halides other than iodide-based additive (X)) per 100 parts by mass of the base resin is preferably 0.05 parts by mass or more and 1 part by mass or less. In this case, a molded product having better heat resistance can be obtained. From the same viewpoint, the amount of metal halide added is more preferably 0.07 parts by mass or more and 0.8 parts by mass or less, and even more preferably 0.1 parts by mass or more and 0.6 parts by mass or less. The amount of metal halide added means the total amount of metal halide added including iodide-based additive (X).

[0038] In the melt-kneading step, various additives such as bubble nucleating agents, antistatic agents, conductivity imparting agents, lubricants, ultraviolet absorbers, flame retardants, metal deactivators, crystal nucleating agents, colorants, and fillers can be appropriately added as necessary. The amount of these various additives added varies depending on the purpose of use of the molded body, but is preferably 25 parts by mass or less per 100 parts by mass of the base resin. More preferably, it is 15 parts by mass or less, even more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less.

[0039] In the melt kneading step, carbon black can be further added, and the polyamide resin melt can contain carbon black. The polyamide resin melt contains carbon black, and the amount of carbon black added is preferably 0.5 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the base resin. In this case, it is possible to produce black foamed beads and molded bodies that are less likely to discolor over time even in a high-temperature environment. Therefore, the foamed beads and molded bodies are suitable for vehicle components (specifically, interior components, exterior components) and the like. From the same viewpoint, the amount of carbon black added to 100 parts by mass of the base resin is more preferably 0.7 parts by mass or more and 7 parts by mass or less, and even more preferably 1.5 parts by mass or more and 5 parts by mass or less. Usually, the addition of carbon black reduces moldability, but in the manufacturing method of the present disclosure, the organic compound additive (A) and the iodide additive (X) are used in a specific amount and a specific ratio, so that excellent moldability can be maintained even when carbon black is added.

[0040] The melt kneading is carried out, for example, in an extruder. The resin temperature is, for example, 250 to 300° C. The resin temperature is the resin temperature at the head portion at the tip of the extruder.

[0041] <Granulation process> In the granulation step, the polyamide-based resin melt is granulated. This produces polyamide-based resin particles. Granulation is carried out, for example, as follows. First, the polyamide-based resin melt is extruded in the form of a strand from an extruder, and the extruded strand is cooled and solidified. Next, the solidified strand is cut. In this manner, the polyamide-based resin melt is granulated, and resin particles can be obtained.

[0042] <Foaming process> As described above, the foaming step is carried out, for example, through a dispersion step, an impregnation step, and a release step. In the foaming step, the resin particles are foamed using a foaming agent to obtain foamed particles. Specifically, the foaming agent is impregnated into the resin particles, and the resin particles containing the foaming agent are foamed by heating, changing the pressure, changing the volume, or the like.

[0043] The blowing agent may be an organic physical blowing agent or an inorganic physical blowing agent. Examples of the organic physical blowing agent include aliphatic hydrocarbons such as propane, butane, pentane, hexane, and heptane; alicyclic hydrocarbons such as cyclopentane and cyclohexane; halogenated hydrocarbons such as chlorofluoromethane, trifluoromethane, 1,1-difluoroethane, 1,1,1,2-tetrafluoroethane, methyl chloride, ethyl chloride, and methylene chloride; and dialkyl ethers such as dimethyl ether, diethyl ether, and methyl ethyl ether. Examples of the inorganic physical blowing agent include carbon dioxide, nitrogen, helium, argon, and air.

[0044] Among the physical blowing agents, from the viewpoints of having little impact on the environment, being non-flammable and having excellent safety, inorganic physical blowing agents are preferred, carbon dioxide or nitrogen are more preferred, and carbon dioxide is even more preferred.

[0045] The foaming step is not particularly limited as long as it involves impregnation of the resin particles with a foaming agent and foaming of the resin particles. For example, the foaming step is carried out by the following method [1] or [2]. [1] A method in which resin particles are impregnated with a foaming agent, the resin particles impregnated with the foaming agent are removed without being foamed, and then heated in a foaming device to obtain foamed particles. [2] A method of obtaining foamed particles by impregnating resin particles dispersed in a dispersion medium (specifically, a liquid) in a sealed device with a foaming agent, raising the temperature to near the softening point of the resin, and then releasing the resin particles together with the dispersion medium outside the device under low pressure. The foaming step is preferably carried out by the method [2] above.

[0046] The method [2] is explained in further detail below.

[0047] The foaming step is preferably carried out through the following steps: dispersing step, impregnation step, holding step, and releasing step. (1) In the dispersing step, resin particles are dispersed in water in a closed vessel to obtain a dispersion. (2) In the impregnation step, the resin particles in the dispersion are impregnated with a physical foaming agent. (3) In the holding step, the dispersion is held at a temperature that is 90° C. lower than the melting point (Tm) of the resin particles (Tm-90° C.) and lower than 50° C. lower (Tm-50° C.) for a holding time of 1 minute to 60 minutes. (4) In the release step, the temperature (Te) of the dispersion liquid immediately before foaming is set to a temperature that is 90°C lower than the melting point (Tm) of the resin particles (Tm - 90°C) or higher and lower than a temperature that is 50°C lower than the melting point (Tm) of the resin particles (Tm - 50°C), and the resin particles containing the foaming agent are released together with water from the sealed container under a pressure lower than the pressure inside the sealed container to cause foaming. The foaming step may include a step other than the dispersing step, the impregnation step, the holding step, and the releasing step, and other components may be added in any of the steps. The impregnation step and the holding step may be performed simultaneously, and the holding step may be performed before or after the impregnation step.

[0048] (Dispersion process) The dispersion step is a step of dispersing resin particles in water in a closed container to obtain a dispersion liquid. The method of dispersing resin particles in water is not particularly limited, and a known method can be used. For example, a dispersion liquid can be obtained by adding resin particles to water while stirring the water using a stirrer, and further stirring. In addition, it is preferable to add a dispersant such as an inorganic substance such as aluminum oxide, tricalcium phosphate, magnesium pyrophosphate, zinc oxide, kaolin, mica, talc, smectite, etc.; or a dispersion assistant such as an anionic surfactant such as sodium dodecylbenzenesulfonate or sodium alkanesulfonate, etc., to the dispersion liquid as necessary. The mass ratio of the resin particles to the dispersant (resin particles / dispersant) is preferably 20 to 2000, more preferably 30 to 1000. In addition, the mass ratio of the dispersant to the dispersion assistant (dispersant / dispersant) is preferably 1 to 500, more preferably 1 to 100.

[0049] (Impregnation process) The impregnation step is a step of impregnating the resin particles in the dispersion with a foaming agent. The resin particles can also be made to absorb water at the same time. The method of impregnating the resin particles with the foaming agent is not particularly limited, but it is preferable to disperse the resin particles in water in a pressurizable closed container such as an autoclave and impregnate the resin particles with the foaming agent. In addition to pressurization, it is preferable to heat the resin particles when impregnating them with the foaming agent, in order to sufficiently impregnate the resin particles with the foaming agent in a short time.

[0050] When pressurization is performed, the impregnation step includes a step in which the pressure inside the sealed container rises from atmospheric pressure to the pressure during impregnation (hereinafter also referred to as impregnation pressure). The step of impregnating the foaming agent includes a step of heating a dispersion liquid in which resin particles are dispersed in water from room temperature to a temperature during impregnation (hereinafter also referred to as the impregnation temperature).

[0051] When the impregnation step is carried out under heating, from the viewpoint of sufficiently impregnating the resin particles with the foaming agent in a short time, the impregnation temperature is preferably 50°C or higher, more preferably 80°C or higher, and is preferably the melting point of the resin particles (Tm(°C)) or lower, more preferably (Tm-20(°C)) or lower.

[0052] In addition, from the viewpoint of impregnating the resin particles with the foaming agent sufficiently in a short time, the pressure during impregnation under pressure (hereinafter also referred to as the impregnation pressure) is set so that the pressure inside the sealed container is preferably 1.5 MPa (G) or more, more preferably 2.5 MPa (G) or more, preferably 7 MPa (G) or less, and more preferably 5 MPa (G) or less by adding the foaming agent to the container containing the dispersion. Note that "(G)" means gauge pressure, and for example, "1.5 MPa (G)" means that the gauge pressure is 1.5 MPa.

[0053] The dispersion step and the impregnation step also serve to allow the resin particles to absorb water. From the viewpoint of allowing the resin particles to sufficiently absorb water and plasticize, the total time of the step of obtaining a dispersion and the step of impregnating a blowing agent is preferably 20 minutes or more, more preferably 30 minutes or more. On the other hand, from the viewpoint of productivity of the expanded beads, the time is preferably 60 minutes or less. In addition, from the viewpoint of allowing the resin particles to sufficiently absorb water and plasticize, the temperature rise rate in the impregnation step is preferably 10° C. / min or less, more preferably 7° C. / min or less. On the other hand, from the viewpoint of productivity of the expanded beads, the temperature rise rate is preferably 1° C. / min or more, more preferably 2° C. / min or more.

[0054] (holding process) The holding step is a step of holding the dispersion at a temperature (Tm-90°C) 90°C lower than the melting point (Tm) of the resin particles and lower than a temperature (Tm-50°C) 50°C lower for a holding time of 1 minute to 60 minutes. The holding temperature of the dispersion in the holding step is 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C) or higher, preferably 80°C lower than the melting point (Tm-80°C) or higher, more preferably 70°C lower than the melting point (Tm-70°C) or higher, and even more preferably 65°C lower than the melting point (Tm-65°C) or higher, and is lower than 50°C lower than the melting point (Tm-50°C), preferably 55°C lower than the melting point (Tm-55°C), more preferably 57°C lower than the melting point (Tm-57°C), and even more preferably 59°C lower than the melting point (Tm-59°C).

[0055] Usually, when manufacturing expanded beads using a general-purpose resin such as a polypropylene resin as a base resin, the temperature is maintained near the melting point of the raw material resin. However, in a manufacturing method of expanded beads using a polyamide resin as a base resin, it is preferable to maintain the temperature at a temperature 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C) or higher and 50°C lower than the melting point (Tm) of the resin particles (Tm-50°C). This is because polyamide resins are hygroscopic, so the resin particles are plasticized by the water used as a dispersion liquid, and the melting point is significantly lowered, and as a result, it is possible to manufacture expanded beads at a temperature significantly lower than the melting point of the resin particles.

[0056] The holding time in the holding step is preferably 1 minute or more, more preferably 5 minutes or more, even more preferably 10 minutes or more, and even more preferably 13 minutes or more, from the viewpoint of uniformly impregnating the resin particles with the blowing agent and obtaining expanded particles having a high closed cell ratio. From the viewpoint of productivity of the expanded particles and the viewpoint of preventing hydrolysis of the polyamide resin, the holding time in the holding step is preferably 60 minutes or less, more preferably 40 minutes or less, even more preferably 30 minutes or less, even more preferably 20 minutes or less, and particularly preferably 18 minutes or less. By holding for the above time, it is possible to obtain expanded polyamide resin particles having a low apparent density and a high closed cell ratio. The holding step can be set in multiple stages within the above temperature range, and it is also possible to slowly increase the temperature within the temperature range over a sufficient period of time. From the viewpoint of easy production, it is preferable to set the temperature in one stage (the holding temperature is constant) within the above temperature range and hold for the above time.

[0057] The holding step is preferably carried out under pressure from the viewpoint of uniformly impregnating the resin particles with the foaming agent, and is preferably maintained at the same pressure as the impregnation pressure. The pressure in the vessel containing the dispersion is preferably 1.5 MPa (G) or more, more preferably 2.5 MPa (G) or more. The pressure in the vessel containing the dispersion is preferably 7 MPa (G) or less, more preferably 5 MPa (G) or less.

[0058] (Release process) The releasing step is a step of foaming the resin particles impregnated with the foaming agent, and is carried out by releasing the resin particles impregnated with the foaming agent together with water into a pressure atmosphere (usually atmospheric pressure) lower than the pressure in the holding step, and foaming is carried out. The releasing step is carried out, for example, following the holding step.

[0059] The temperature Te of the dispersion immediately before foaming (hereinafter also referred to as the foaming temperature) is preferably 90° C. lower than the melting point (Tm) of the resin particles (Tm-90° C.) or higher, more preferably 80° C. lower than the melting point (Tm-80° C.) or higher, even more preferably 70° C. lower than the melting point (Tm-70° C.) or higher, and even more preferably 65° C. lower than the melting point (Tm-65° C.) or higher, from the viewpoint of obtaining foamed particles having a low apparent density and a high closed cell ratio. In addition, the foaming temperature is preferably less than 50° C. lower than the melting point (Tm) of the resin particles (Tm-50° C.), more preferably 55° C. lower than the melting point (Tm) of the resin particles (Tm-55° C.), even more preferably 57° C. lower than the melting point (Tm-57° C.), and even more preferably 59° C. lower than the melting point (Tm-59° C.).

[0060] The pressure immediately before the release in the release step (foaming pressure) is preferably 0.5 MPa (G) or more, more preferably 1.5 MPa (G) or more, and even more preferably 2.5 MPa (G) or more. The foaming pressure is preferably 10 MPa (G) or less, more preferably 7 MPa (G) or less, and even more preferably 5 MPa (G) or less.

[0061] [Foam particles] (Apparent density) The apparent density of the foam particles is 50 to 200 kg / m 3 In this case, the expanded beads and the molded article have excellent light weight and can fully exhibit the mechanical properties of the polyamide resin. From the viewpoint of further improving this effect, the apparent density of the expanded beads is preferably 55 to 150 kg / m 3 More preferably, it is 60 to 130 kg / m 3 The apparent density is measured as follows. First, a sample of about 500 cm2 is left for 2 days under the conditions of 50% relative humidity, 23°C, and 1 atm. 3 The mass W1 of the foamed beads is measured. Next, a measuring cylinder containing water at a temperature of 23°C is prepared, and the foamed beads whose mass has been measured are submerged in the measuring cylinder using a wire net. Taking into account the volume of the wire net, the volume V1 of the foamed beads is read from the rise in the water level [unit: cm 3] is measured, and the mass W1 [g] of the foamed particles is divided by the volume V1 (W1 / V1), and the unit is [kg / m 3 The apparent density of the expanded beads is calculated by converting this to

[0062] [Method of manufacturing molded body] The expanded beads are molded in a mold to obtain a molded article, which is formed by fusing the expanded beads together.

[0063] The in-mold molding method can be a conventionally known method, but it is preferable to use heating with steam. The polyamide resin in the expanded beads absorbs water and plasticizes by steam, making it possible to reduce the molding pressure. If the obtained molded body is dried to remove the moisture, it will return to the original physical properties of the polyamide resin, and the molded body will have high heat resistance.

[0064] In-mold molding is carried out, for example, as follows. First, the foamed particles are filled into a mold. Next, steam is supplied into the mold to heat and fuse the foamed particles. After heating, the pressure is released and the molded body is cooled with water until the surface pressure due to the foaming force of the molded body drops to a predetermined pressure (for example, 0.02 to 0.04 MPa (gauge pressure)), after which the mold is opened and the molded body is removed from the mold.

[0065] [Molded body] (Thickness) The expanded polyamide resin beads obtained by the manufacturing method of the present disclosure have excellent moldability and are therefore suitable for molding a thick (i.e., thick) molded article. Specifically, the thickness of the expanded bead molded article is preferably 30 mm or more, and more preferably 35 mm or more.

[0066] (density) From the viewpoint of further improving the light weight, the density of the molded body is 40 to 200 kg / m 3 is preferably 45 to 150 kg / m 3 More preferably, it is 50 to 120 kg / m 3The density of the molded body is calculated by dividing the mass of the molded body by the external dimensions, and expressed in units of [kg / m 3 ] can be calculated by converting

[0067] (Fusion rate) From the viewpoint of improving the appearance and mechanical properties of the molded article, the fusion rate of the molded article is preferably 90% or more. The method for measuring the fusion rate will be described later.

[0068] (Shrinkage rate after heating) From the viewpoint of more sufficiently preventing shrinkage in a high-temperature environment, the shrinkage rate after heating at a temperature of 160°C for 20 days is preferably 3% or less, more preferably 1% or less, and even more preferably 0.4% or less. The shrinkage rate of the molded product after heating can be adjusted to the above range by using the iodide-based additive (X) and the organic compound-based additive (A) in combination as described above. The method for measuring the shrinkage rate will be described later. EXAMPLES

[0069] Next, the present invention will be described in more detail with reference to examples. However, the present invention is not limited to these examples, and various modifications are possible without departing from the gist of the present invention.

[0070] [Example 1] [Production of resin particles] 100 parts by weight of polyamide resin, 0.2 parts by weight of hindered phenol compound, 0.2 parts by weight of organic phosphorus compound, 0.05 parts by weight of copper iodide, 0.2 parts by weight of potassium iodide, and 0.3 parts by weight of bubble nucleating agent (specifically, talc) were fed to an extruder, and melt-kneaded to obtain a melt-kneaded product. Note that "UBE Nylon 6434B" manufactured by Ube Industries, Ltd. was used as the polyamide resin, N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide] ("Irganox1098" manufactured by BASF Japan, Ltd.) was used as the hindered phenol compound, tris(2,4-di-t-butylphenyl)phosphite ("Irgafos168" manufactured by BASF Japan, Ltd.) was used as the organic phosphorus compound, and talc ("Talcan Powder KHP-125B" manufactured by Hayashi Kasei Co., Ltd.) was used as the bubble nucleating agent. The molten mixture was extruded from the small holes in the nozzle attached to the tip of the extruder as a strand with a circular cross section, and the extruded strand was cooled with water, then cut into pieces with an average mass of 2 mg each using a pelletizer, and dried to obtain pellet-shaped resin particles. The melting point of the resin particles was 186°C. The polyamide resin "6434B" is a polyamide 6 / 66 / 12 copolymer (nylon 6 / 66 / 12), with a melting point (Tm) of 188°C and a density of 1.14g / cm 3 , flexural modulus: 1070 MPa, product name: UBE Nylon 6434B.

[0071] [Production of foamed beads] In a 5-liter autoclave equipped with a stirrer, 500 g of resin particles and 3.5 liters of water as a dispersion medium were charged, and further, 0.3 parts by mass of kaolin as a dispersant and 0.004 parts by mass of sodium alkylbenzene sulfonate as a surfactant were added to 100 parts by mass of resin particles. While stirring the contents in the autoclave, the temperature was raised from room temperature (specifically, 23°C) to the impregnation temperature (131.5°C), and carbon dioxide as a foaming agent was pressed into the autoclave until the pressure in the autoclave reached the impregnation pressure (4.0 MPa (G)). At this time, the temperature rise time from room temperature (23°C) to the impregnation temperature (131.5°C) was 40 minutes. Next, the temperature was held at 131°C and 4.0 MPa (G) for 15 minutes. The resin particles impregnated with the foaming agent were then released together with the dispersion medium under atmospheric pressure (0.1 MPa) to expand the resin particles, thereby obtaining expanded particles. The expansion temperature (temperature of the dispersion liquid immediately before expansion) was 131.5°C. The expanded particles were then cured in an oven at 60°C for 24 hours, and then slowly cooled to 23°C. The expanded particles thus obtained were used for the evaluations described below and for the production of molded bodies.

[0072] [Production of Molded Products] Next, a molded product was produced using the expanded beads. Specifically, after clamping the mold, the expanded beads were filled into a flat mold measuring 200 mm in length, 65 mm in width, and 40 mm in thickness, and molded in the mold by steam heating to obtain a plate-shaped expanded molded product.

[0073] The heating method was as follows: with the drain valves on both sides of the mold open, steam was supplied for 5 seconds to perform preheating (exhaust process), then steam was supplied from the moving mold with the drain valve on the fixed side open, and then steam was supplied from the fixed mold with the drain valve on the moving side open, after which the exhaust valve was closed and heating was performed up to a molding heating steam pressure of 0.12 MPa (molding pressure = molding steam pressure). After heating, the pressure was released and the molded body was cooled with water until the surface pressure due to the foaming force of the molded body dropped to 0.02 MPa (gauge pressure), after which the mold was opened and the molded body was removed from the mold. It was then left to stand in an oven at 80°C, and after 24 hours it was taken out to obtain a molded body.

[0074] <Evaluation of expanded particles> The expanded beads were evaluated as follows, and the results are shown in the table below. (Apparent density) First, a 500 cm sample was left for 2 days under the conditions of 50% relative humidity, 23°C, and 1 atm. 3 The mass W1 of the expanded beads was measured. Next, a measuring cylinder containing water at a temperature of 23°C was prepared, and the expanded beads whose mass had been measured were submerged in the measuring cylinder using a wire net. Taking into account the volume of the wire net, the volume V1 of the expanded beads read from the rise in the water level [unit: cm 3 ] is measured, and the mass W1 [g] of the foamed particles is divided by the volume V1 (W1 / V1), and the unit is [kg / m 3 The apparent density of the expanded beads was calculated by converting the density into the mass ratio (μm).

[0075] <Evaluation of moldability> The moldability was evaluated by changing the molding pressure while molding the expanded beads in a mold and evaluating the moldable range. First, the molding pressure was changed by 0.02 MPa between 0.10 and 0.18 [MPa (G): gauge pressure)], and molding in a mold was performed at a total of four molding pressures. Next, the molded bodies manufactured at each molding pressure were evaluated for fusion, recovery, and surface properties (center of molded body, corner of molded body). When there are two or more molding pressures capable of molding a molded body that passes all the above evaluations, it was evaluated as "A", when there is one molding pressure capable of molding a molded body that passes all the above evaluations, it was evaluated as "B", and when there is no molding pressure capable of molding a molded body that passes all the above evaluations, it was evaluated as "C".

[0076] (Fusing ability) The fusion rate was measured to evaluate the fusion property of the molded body. A fusion rate of 80% or more was rated as "A (pass)", a fusion rate of 40% or more but less than 80% was rated as "B (fail)", and a fusion rate of less than 40% was rated as "C (fail)". The fusion rate of the molded body was measured by the following method. A flat molded body was used as a test piece, and a cut was made with a cutter knife on one of its main surfaces (i.e., the surface with the widest area) at a position that divides the vertical length of the molded body in half in the thickness direction to a depth of about 10 mm, and the molded body was folded and broken from the cut. The ratio (m / n×100[%]) of the number of foamed particles that had been broken on the fracture surface to the number n of all foamed particles present on the fracture surface, that is, the material destruction rate, was calculated. Note that when the molded body could not be broken even by folding it, the fusion rate was determined to be 100%. The above measurement was performed five times using different test pieces, and the material destruction rate for each was calculated, and the arithmetic average of the material destruction rates was determined as the fusion rate.

[0077] (Recoverability) After leaving the molded body for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, the thickness of the central part of the main surface of the flat molded body (i.e., the surface with the largest area) and the thickness of the four corners of the main surface were each measured. If the ratio of the thickness of the central part to the thickest part of the four corners was 90% or more, it was evaluated as "A (pass)", and if it was less than 90%, it was evaluated as "C (fail)".

[0078] (superficial) ·Central part The center of the surface of the flat plate-shaped molded article (specifically, the center of each surface of the molded article) was visually inspected, and the appearance was evaluated according to the following criteria. A (pass): The center of the surface was beautiful and had excellent appearance. B (failed): Voids (specifically, gaps between foam particles) were found in the center of the surface, and the appearance was poor. C (fail): Voids (specifically, gaps between foam particles) were clearly observed in the center of the surface, and the appearance was poor. Corners The corners of the surface of the flat molded product (within a radius of 10 mm from the corner of the molded product) were visually inspected and the appearance was evaluated according to the following criteria. A (Pass): The corners of the surface are beautiful and have an excellent appearance. B (failed): Voids (specifically, gaps between foam particles) were found in the corners of the surface, and the appearance was poor. C (fail): Voids (specifically, gaps between foam particles) were clearly observed at the corners of the surface, and the appearance was poor.

[0079] <Evaluation of Molded Products> The expanded beads were evaluated as follows, and the results are shown in the table below. (density) The mass of the molded body is divided by the external dimensions and expressed in units of [kg / m 3 The density of the green body was calculated by converting the density of the green body into the mass per unit area (molecular weight).

[0080] (Molding shrinkage rate of molded body) After molding, the molded body was heated in a dryer at 160°C for 20 days. Thereafter, the dimensions of the molded body were measured, and the length, width, and thickness were designated as a', b', and c', respectively, and the length, width, and thickness of the dimensions (internal dimensions) of the mold were designated as a, b, and c, respectively. The value shown by the following formula was taken as the mold shrinkage rate (%) of the molded body. The smaller the mold shrinkage rate value of the molded body, the more the mold shrinkage is suppressed. (Formula) Mold shrinkage rate (%) = [|(a-a') / a| + |(b-b') / b| + |(c-c') / c|] x 100 / 3

[0081] [Example 2] This is the same as Example 1, except that the amount of the hindered phenol compound added per 100 parts by mass of the base resin was changed to 0.1 parts by mass, and the amount of the organophosphorus compound added per 100 parts by mass of the base resin was changed to 0.1 parts by mass.

[0082] [Example 3] The procedure was the same as in Example 1, except that 2.5 parts by mass of carbon black was further added per 100 parts by mass of the base resin during melt-kneading.

[0083] [Example 4] The same as in Example 1, except that the amount of the organic phosphorus compound added was changed to 0.4 parts by mass per 100 parts by mass of the base resin.

[0084] [Example 5] This is the same as Example 1, except that the amount of the hindered phenol compound added per 100 parts by mass of the base resin was changed to 0.4 parts by mass, and the amount of the organophosphorus compound added per 100 parts by mass of the base resin was changed to 0.4 parts by mass.

[0085] [Example 6] This is the same as Example 1, except that the amount of the hindered phenol compound added per 100 parts by mass of the base resin was changed to 0.6 parts by mass, and the amount of the organophosphorus compound added per 100 parts by mass of the base resin was changed to 0.6 parts by mass.

[0086] [Comparative Example 1] The same as in Example 1, except that the organic compound additive (A) (hindered phenol compound, organic phosphorus compound) and the iodide additive (X) (copper iodide, potassium iodide) were not fed to the extruder during melt kneading.

[0087] [Comparative Example 2] The procedure was the same as in Example 1, except that the organic compound-based additives (A) (hindered phenol compounds, organic phosphorus compounds) were not fed to the extruder during melt-kneading.

[0088] [Comparative Example 3] The procedure was the same as in Example 1, except that the iodide-based additive (X) (copper iodide, potassium iodide) was not fed to the extruder during melt-kneading.

[0089] [Comparative Example 4] The same as Example 1 was used, except that the amount of organic compound-based additive (A) (hindered phenol compound, organic phosphorus compound) added was reduced and the amount of iodide-based additive (X) (copper iodide, potassium iodide) added was increased.

[0090] [Comparative Example 5] The same as in Example 1, except that the amount of the iodide-based additive (X) (copper iodide, potassium iodide) added was reduced.

[0091] [Comparative Example 6] The procedure was the same as in Example 1, except that the amount of the organic compound-based additive (A) (hindered phenol compound, organic phosphorus compound) added was increased.

[0092] [Table 1]

[0093] [Table 2]

[0094] [Table 3]

[0095] [Table 4]

[0096] [Table 5]

[0097] [Table 6]

[0098] As can be seen from Tables 1 and 2, the expanded beads of the Examples are expanded to a high degree, have good light weight, and are excellent in moldability. The molded articles of the Examples have low density and good light weight, and also have small shrinkage after heating and excellent heat resistance. As can be seen from Tables 3 to 6, the molded articles of the Examples have excellent surface properties and are obtained over a wide range of molding pressures. The molded articles of the Examples also have excellent moldability even under low molding pressure conditions. This is because, in the Examples, the organic compound-based additive (A) and the iodide-based additive (X) are added to the base resin at a predetermined ratio during melt kneading. In addition, in this example, a terminal blocking agent such as a carbodiimide compound is not used, and a polyamide resin with no functional group at the molecular chain end (i.e., easily hydrolyzed) is used, but the moldability is excellent. This is believed to be because the organic compound additive (A) and the iodide additive (X) are used in combination at a predetermined ratio as described above. It is believed that the use of a terminal blocking agent suppresses hydrolysis, thereby further improving moldability. For the density and shrinkage rate of the molded bodies in Tables 1 and 2, the molded body obtained at the lowest molding pressure among the molded bodies that were all evaluated as passing in Tables 3 to 6 was used, and for the comparative examples in which no molded bodies were all evaluated as passing, the molded body obtained at the molding pressure with the best evaluation was used.

[0099] In Comparative Example 1, since the organic compound-based additive (A) and the iodide-based additive (X) are not added, the heat resistance is poor and the moldability is also poor. In Comparative Example 2, although the iodide-based additive (X) is added, the organic compound-based additive (A) is not added, and therefore the moldability is insufficient.

[0100] In Comparative Example 3, although the organic compound-based additive (A) is added, the iodide-based additive (X) is not added, and therefore the heat resistance is poor and the moldability is also insufficient.

[0101] In Comparative Example 4, the amount of the organic compound additive (A) added was small, and the ratio of the amount of the organic compound additive (A) added to the amount of the iodide additive (X) added was too low, resulting in insufficient moldability in the mold. In Comparative Example 5, the amount of the iodide-based additive (X) was small, and the ratio of the amount of the organic compound-based additive (A) to the amount of the iodide-based additive (X) was too high, resulting in poor heat resistance and insufficient moldability in the mold. In Comparative Example 6, the amount of the organic compound additive (A) was too large, and the ratio of the amount of the organic compound additive (A) to the amount of the iodide additive (X) was too high, resulting in insufficient moldability in the mold.

[0102] In this way, by adding an organic compound-based additive (A) consisting of a hindered phenol compound and / or an organic phosphorus compound, and an iodide-based additive (X) consisting of copper iodide or copper iodide and potassium iodide to the base resin during melt kneading, and adjusting the amounts added, it is possible to produce a polyamide resin foamed molded product with excellent heat resistance and light weight, and to obtain foamed particles with excellent moldability.

Claims

1. A method for producing expanded polyamide-based resin beads using a polyamide-based resin as a base resin, comprising the steps of: a step of preparing polyamide-based resin particles by granulating a melt of a polyamide-based resin obtained by melt-kneading the base resin, an organic compound-based additive (A) consisting of a hindered phenol compound and / or an organic phosphorus compound, and an iodide-based additive (X) consisting of copper iodide or copper iodide and potassium iodide; and a step of expanding the polyamide-based resin particles using a foaming agent to obtain expanded polyamide-based resin particles, the amount of the organic compound-based additive (A) added is 0.05 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the base resin, A method for producing expanded polyamide resin beads, wherein the ratio of the amount of the organic compound-based additive (A) to the amount of the iodide-based additive (X) is 0.3 or more and 7 or less.

2. 2. The method for producing expanded polyamide resin beads according to claim 1, wherein a ratio of the amount of the organic compound-based additive (A) to the amount of the iodide-based additive (X) is 1 or more and 4 or less.

3. 3. The method for producing expanded polyamide resin beads according to claim 1, wherein the polyamide resin melt contains the hindered phenol compound (A1) and the organophosphorus compound (A2) as the organic compound additive (A), and a ratio of the amount of the organophosphorus compound (A2) to the amount of the hindered phenol compound (A1) is 0.5 or more and 2 or less.

4. 3. The method for producing expanded polyamide resin beads according to claim 1, wherein the amount of the iodide additive (X) added is 0.1 parts by mass or more per 100 parts by mass of the base resin.

5. 3. The method for producing expanded polyamide resin beads according to claim 1, wherein the polyamide resin melt further contains carbon black, and the amount of the carbon black added is 0.5 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the base resin.

6. A method for producing a polyamide resin foamed article, comprising molding the expanded polyamide resin beads produced by the method according to claim 1 or 2 in a mold.

Citation Information

Patent Citations

  • Polyamide resin prefoamed particle, polyamide resin foamed molded article, and method for manufacturing polyamide resin foamed molded article

    WO2020196893A1